COMPARATIVE ASSESSMENT OF INNOVATIVE ACTIVITY OF RUSSIAN AND FOREIGN FIRMS - A. Krasnikov (Вестник Северо-Кавказского федерального университета)
Achieving stable rates of economic growth and integration into global space suggests the need for fulfilling innovative potential of not only certain firms or regions but also the whole country. The research deals with relevant comparative information about innovative activity of Russian and foreign firms. The aim of the survey is to assess national and foreign innovative system. Furthermore, the reserves setting for improvement of development eficiency of Russian irms is given. The research presents the situation which relates to development of innovative processes in Russian and abroad, the assessment ofgovernment support of national innovative systems is pointed out.